(untitled) (Medico Legal Update, 2020)
Cystic Echinococcosis is the most important zoonotic parasite with community health in addition to financial problem. This study was planned to detect a morphological structure of protoscolices of hydatid cysts that isolated from slaughtered sheep that exposure to Tinidazole and Bendaziole, and showed a different number and shape of hydatid cysts from different organs like; lungs and livers, with viability result of protoscolices. A clear be to found a hydatid sand and protoscolices distribution, and germinal layer without any treatment, all normal in shape and structure, but samples treated with drug Tinidazole and Bendaziole. It is a clear found distraction of protoscolices, and germinal layer of hydatid cyst in shape and structure. The current study explain some different between the liquid and germinal layer of cyst when sample treated with these drugs and other not treated in shape and morphological form of protoscolices.